Preoperative Doppler ultrasound examination of saphenous veins - Buczkowski, Piotr; Puślecki, Mateusz; Szajkowski, Rafał; Żabicki, Bartosz; Misterski, Marcin; Urbanowicz, Tomasz; Perek, Bartłomiej; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Background : In recent decades we have seen steady progress of medical services due to continuous technological development and the extensive cooperation of many medical fields. Aim: The aim of this study was to evaluate the usefulness of preoperative ultrasonography (USG-Doppler) of the saphenous vein used as aorto-coronary grafts in CABG. Materials and methods : The study included 200 patients who underwent CABG using their own saphenous vein. Patients were randomly divided into two groups. In group I (n = 100) before harvesting the saphenous vein morphology was assessed by ultrasound (Doppler) and in control group II (n = 100), veins were analysed only by the preoperative physical examination. In both groups the traditional method of harvesting the saphenous vein was used. An ultrasound evaluation was used: diameter, depth of course, location of branches, flexibility, and other pathologies. In two selected groups of patients we measured time of preparation, length of graft and length of skin cut. We evaluated the rate of wound healing. Results : There were no significant differences in vein length used for CABG (34.1 ±8.5 cm and 34.7 ±6.7 cm, respectively in group I and II), and the total length of the skin cut was significantly lower in group I (34.1 ±8.5 cm vs 50.2 ±7.0 cm in group II). Total time taken to prepare the saphenous vein for CABG was significantly shorter (p < 0.05) in group I (63.3 ±16.4 minutes) than in group II (76.7 ±18.9 minutes). In group II two patients had wound infections, while in group I we did not observe any complications. The incidence of haematoma, swelling and pain did not differ significantly between groups. Conclusions : The preoperative ultrasound-Doppler examination of saphenous veins helps to choose the optimal segment of vein used for heart revascularization, which may increase the long-term benefits of CABG.